Study of Korean and Mongolian Derived Words: (Using mimetic words as an example) - Chimeddorj, Duurenjargal (Mongolian Journal of Humanities and Social Sciences, 2023)
Korean is an agglutinative language belonging to the Altaic language. And there are many mimetic words in the vocabulary. Mimetic words, which are often used in literary works, have unique characteristics. In this paper, we will examine how verbs, adjectives, and nouns are formed from mimetic words stems in Korean and Mongolian. As for the words derived from the mimetic stem of Mongolian, 625 verbs, 274 adjectives, and 6 nouns were studied by referring to Sh. Narantuya's Explanatory dictionary of mimetic words and the words derived from these words were studied. In the case of Korean, 1,689 verbs, 914 adjectives, and 99 nouns derived from mimetic words stems were classified according to suffixes in the Korean explanatory dictionary published by the National Institute of the Korean Language. Among words formed from mimetic words stems in Mongolian and Korean, there are the most verbs and the fewest derived nouns.In order to find out nouns formed in mimetic stems in Mongolian, in-depth research on the structure and etymology of words is essential. Otherwise, it is not as clear as the result of the creation of verbs and adjectives in the mimetic stem. Солонгос, монгол хэлний үүсмэл үгсийг судлах нь (Дүрслэх үгийн жишээн дээр) Хураангуй: Солонгос, монгол хэлний авиа дуурайх, дүрслэх үгс нь нэн эртний уугуул үгс байх бөгөөд шинэ үг бүтэхэд чухал үүрэгтэй. Эдгээр үгсийн язгуурт үүсмэл үг бүтээх дагавар залган үйл үг, нэр үг, тэмдэг нэр бүтсэн байдаг. Тухайлбал, солонгос хэлний дүрслэх дан болон давтсан хэлбэрт “거리다[georida], 대다[daeda], 이다[ida]” зэрэг дагавар залган үйл үг, “하다[hada], -업[eob]” дагавар залгаж, тэмдэг үг, нэр үг бүтээх “-이[-i], -질[-jil], -쇠[soe], – 아기, 어기[-agi,-eogi], -아지[-aji]” дагавар залган нэр үг бүтэж байна. Тэгвэл монгол хэлэнд дүрслэх язгуураас хэрхэн жинхэнэ нэр, үйл үг, тэмдэг нэр бүтэж буйг харьцуулан судлахыг зорилоо. Түлхүүр үг: Дүр байдал, дагаврын арга, үг бүтэх ёс, жинхэнэ нэр, үйл үг, тэмдэг нэр